Impact of Using SERVPERF Scale to Measure the Quality of Educational Services on Students' Satisfaction at Ibb University - Yemen - Abdullah A. Al-Awlaki (University of Science and Technology, Yemen, 2018)
This study examined the effect of the quality of educational services on improving students' satisfaction in Ibb University. To achieve this objective, a survey checklist was used to collect the required initial data from a sample of 375 students studying at the colleges of Ibb University using the SERVPER scale. The results showed a considerable weakness in the quality of educational services (tangible aspects, reliability, responsiveness, safety, security, and empathy), which are provided by Ibb University, as well as their irrelevance to the interests and expectations of the students. The results also revealed that the quality of educational services has a significant relationship with the improvement of students' satisfaction in Ibb University. Keywords: Quality of educational services, Students' satisfaction, Ibb University.